2020
DOI: 10.24059/olj.v24i4.2335
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Student Perceptions of Flipgrid in Online Courses

Abstract: Asynchronous video-based discussions have affordances that can address some of the constraints of asynchronous text-based discussions. However, little research has been conducted on the use of asynchronous video-based discussions in online courses. As a result, the purpose of this exploratory study was to investigate students’ perceptions of using Flipgrid for asynchronous video-based discussions in fully online courses. We used a cross-sectional survey design to survey 79 students who used Flipgrid in a fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 41 publications
(70 reference statements)
11
78
0
1
Order By: Relevance
“…The authors concluded that students put in time and effort and were engaged in the Flipgrid activities. Setting aside the differences betweenJohnson & Skarphol's (2018) study and the current one, the results are similar and indicate high student engagement Lowenthal and Moore (2020). conducted a survey study to research students' perceptions of using Flipgrid for asynchronous discussions in online courses.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The authors concluded that students put in time and effort and were engaged in the Flipgrid activities. Setting aside the differences betweenJohnson & Skarphol's (2018) study and the current one, the results are similar and indicate high student engagement Lowenthal and Moore (2020). conducted a survey study to research students' perceptions of using Flipgrid for asynchronous discussions in online courses.…”
supporting
confidence: 54%
“…Another survey study (n=79) conducted by Lowenthal and Moore (2020) suggests that learners liked using Flipgrid and found value in participating in video-based asynchronous discussions.…”
Section: Introductionmentioning
confidence: 99%
“…McLain also reported an increase in students' perceived confidence in their English-speaking skills. Lowenthal & Moore (2020) investigated graduate students' perceptions of the use of FG in online courses. Students in their study found FG to be a valuable tool for promoting social presence through asynchronous video discussions.…”
Section: Review Of the Literature Flipgridmentioning
confidence: 99%
“…He has interest in, and experience with, various teaching and learning communication technologies. However, he also believes that no communication technology is inherently better than another, and that video is not a panacea and should be used intentionally and selectively (see Belt & Lowenthal, under review;Belt & Lowenthal, 2021;Lowenthal, under review;Lowenthal, 2021;Lowenthal et al, 2022;Lowenthal & Moore, 2020). He approached this study with an interest in better understanding how faculty experiences during COVID-19 might influence their perceptions and future use of synchronous video-based communication technology and, in turn, its influence on the future of online learning.…”
Section: Positionality Trustworthiness and Credibilitymentioning
confidence: 99%